Analisis Kebutuhan Fasilitas Integrasi Antarmoda Dalam Upaya Peningkatan Pelayanan Di Stasiljn Tugu Yogyakarta - Lestari, Sri; Romadhona, Prima Juanita (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
In an effort to impraue passenger rail senrice to the Monument station, Jogjakarta, the need faradditional supporting infrastructure and facilities for passengers wlw will continue the jaurnei; withother rrwdes. T17erefare necessan; to know haw Jar the perception of the needs of the facility at StationIntegration Antamwda rrwnument. T11is study aimed to obtain the rrwst SUTJPOrtive infrastructurefor impraved seroice to users within the framework of Jogjakarta Tugu Station inter-modal integration.T11is studi using UMDEP 7.0 software analysisi. Based on modeling and field conditions, thereis the possibiliti; of design planning additionnl locations for tlze integration of inter-modal Jaciliti; atTugu Stntion, Yogi;nknrtn. Additional facilities nre conducted nt Tugu Stntion east parking area.Trans ]ogja placement nnd DAMRI stop there on tlze north side entrance to Monument Station or onthe sidewalk 1 st of Road Mangkubumi.